Risk Factors of HIV among Voluntary Counseling and Testing Centers Clients, Elgenina Town, West Darfur, Sudan. - Ahmed,, M. Hussein; Ahmed, Mokhtar Osman Mohammed; Dawria,, Adam (Journal of Clinical Research In HIV AIDS And Prevention, 2019)
This study was conducted in two (VCTs) at Elgenina town, the capital of West Darfur State in Sudan in period from November 2010 to February 2011, the study included all people attending VCTs in Elgeniena town for voluntary checking one hundred and fifty clients who visited the (VCT) centers and volunteered were included in this study, nonprobability sample, 150 volunteers was taken and covered all ages, One ml of blood was taken from each of the study sample and tested by rapid Immune Chromatographic (ICT) for HIV, a structured questionnaire was designed and the interviewed after a written consent to participate in the study was signed, data was analyzed using the SPSS statistical programmer and for possible association between study variables, the Chi square test was used, the study showed that 35 volunteers (23.33%) were positives, of whom 54.3% 19 were males. People having more than one sex partner were high 63.6% with statistically significant factor of getting infection (P.value = 0.00). Also, practicing unsafe sex were 5.2% another major risky (P.value = 0.00). Among the HIV positive cases 34.3% were drug users, compared to 20.9% from the HIV negatives (p. value = 0.10). There is no relation between education level and infection with HIV (p .value = 0.154). Forty two percent of the participants were single, 30% married, 10% divorced, 7.3% widows and 10.7% were separate